Hydrothermal dewatering of low-rank coals: Influence on the properties and combustion characteristics of the solid products. (1st September 2018) - Ullah, Habib; Liu, Guijian; Yousaf, Balal; Ali, Muhammad Ubaid; Abbas, Qumber; Zhou, Chuncai; Rashid, Audil
Abstract: The presence of increased moisture content, low energy density and maximum spontaneous combustion tendency has raised serious environmental issues, which are obstacles to large scale utilization of coals. Hydrothermal dewatering (HTD) is a promising method for upgrading low rank coals (LRCs). The influences of HTD, executed at different temperatures on solid product yield, removal rate of elements, organics and inorganics, and combustion characteristics in LRCs were studied. HTD treatment of LRCs was carried out in 2 L cylindrical autoclave at 200–300 °C for 1 h. For upgraded coals, the inherent moisture and oxygen content decreased significantly while fixed carbon content and calorific value increased. FTIR results indicate the conversion of LRCs near to high-rank coals (HRCs). The organic matter was removed due to loss of Methylene, Methyl groups and O-containing functional groups, whereas inorganic matter was removed mainly in the forms of Fe and Ca-containing minerals. The upgraded coals had higher ignition and burnout temperatures, while their combustion was shifted and delayed toward higher temperature zone. Activation energy of treated coals increased in ignition stage while decreased in combustion segment. Prominent changes were found in coal structure, composition, rank, and combustion characteristics at HTD temperature of 300 °C. Highlights: Low rank coals (LRCs) are efficiently upgraded by hydrothermal dewatering (HTD). Organics and inorganics removal increased with increased HTD temperature. FTIR spectra indicate coal rank improvement and microstructure change after HTD. Hydrothermally dewatered coals faced trouble in ignition but burn easily. More evident effect on coal rank improvement and combustion features are obtained.